2010
DOI: 10.1590/s0034-89102010000300011
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for osteoporotic fractures and low bone density in pre and postmenopausal women

Abstract: OBJECTIVE: To estimate the prevalence and analyze risk factors associated to osteoporosis and low-trauma fracture in women. METHODS: Cross-sectional study including a total of 4,332 women older than 40 attending primary care services in the Greater São Paulo, Southeastern Brazil, between 2004 and 2007. Anthropometrical and gynecological data and information about lifestyle habits, previous fracture, medical history, food intake and physical activity were obtained through individual quantitative interviews. Low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
60
0
14

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(78 citation statements)
references
References 28 publications
4
60
0
14
Order By: Relevance
“…Estudos prévios realizados no Brasil 22, 24,25 , no Paquistão 26 e no Irã 27 mostraram que a prevalência de osteoporose nas mulheres é quase o dobro em relação aos homens. Outra justificativa é porque as mulheres apresentam maior velocidade de perda óssea após a menopausa devido à diminuição hormonal significativa nos níveis de estrogênio 9 .…”
Section: ▄ Discussãounclassified
“…Estudos prévios realizados no Brasil 22, 24,25 , no Paquistão 26 e no Irã 27 mostraram que a prevalência de osteoporose nas mulheres é quase o dobro em relação aos homens. Outra justificativa é porque as mulheres apresentam maior velocidade de perda óssea após a menopausa devido à diminuição hormonal significativa nos níveis de estrogênio 9 .…”
Section: ▄ Discussãounclassified
“…3 In addition to this, post-menopausal women suffer from osteoporosis and osteoporotic fractures at a higher frequency than pre-menopausal women. 4 Through adult life there is a dynamic progress which is called "bone remodeling". Bone remodeling is well established throughout the literature and involves both systemic and non-systemic factors.…”
Section: Introductionmentioning
confidence: 99%
“…Concerning the association between osteoporosis and abdominal obesity, previous studies reported negative relationships between measurements of abdominal obesity and lower bone mass 33,34 . The pathways by which abdominal obesity affects bone tissue are not completely understood yet, but involve the action of inflammatory markers produced by adipose tissues, which affect the osteoblasts/osteoclasts ratio in the bone matrix 35 , leading to lower bone mass. In regards to lifestyle factors, current physical activity was associated with lower occurrence of osteoporosis, findings similar to those of other studies 16,36 .…”
Section: Discussionmentioning
confidence: 99%